Analisis Break Even Point Sebagai Alat Perencanaan Laba pada Perusahaan Browcyl Brownis Pisang Khas Makassar - Rosida Rosida (Al-Kharaj: Journal of Islamic Economic and Business, 2019)
This article is the result of a study that analyzes break even point as a profit planning tool at the Makassar Banana Browcyl Brownis company. Located on Jl. A.P. Pettarani Kota Makassar, research using descriptive method based on case studies aims to determine the value of each variable, either one variable or more independent in nature without making a relationship or comparison with other variables. Data processing is done by looking for contribution margin value, break even point and margin of safety. The results of this study indicate that in 2017 the break-even achieved by the company was Rp. 72,070,308.51 and BEP per kg of Rp. 1.018. In 2018 the break-even point reached by the company was Rp. 69,612,903.23 and BEP per kg of 2,308. The margin of safety in 2017 to 2018 has increased 83% to 86%. Sales in 2017 and 2018 have reached the calculated sales target. This research is important because it allows companies to conduct business expansion or increase production in accordance with the company's capacity